Facile and Efficient Construction of Water‐Soluble Biomaterials with Tunable Mesoscopic Structures Using All‐Natural Edible Proteins. (14th April 2019) - Wang, Tao; Chen, Xianfu; Zhong, Qixin; Chen, Zhengxing; Wang, Ren; Patel, Ashok R.
Abstract: Developing biomaterials with tunable chemical and physical properties using natural molecules is central to a wide range of applications, yet the manipulation of biomacromolecular structures toward tailorable architectures remains limited. Herein, for the first time, a set of all‐natural, ubiquitous edible protein‐based nanostructures with fascinating tunability in their mesostructures easily transformed from 3D nanonet to 2D thin sheet and to nanoparticles is presented. This is achieved by simply dissolving casein micelles and various amounts of rice proteins in an alkaline solution (pH 12), followed by neutralization to form mesoscale protein composites. The structural transitions as a result of tuning the two protein ratio are confirmed by atomic force microscopy, cryo‐transmission electron microscopy, and X‐ray diffraction. When loaded with a hydrophobic model drug, apigenin (also a food‐sourced molecule), the mesoscopic structure determines the in vivo anti‐tumor activity of apigenin. The availability and biocompatibility of the studied materials, plus simple preparation and easy manipulation of the mesostructures, have promise in designing on‐demand biochemical‐carrying materials with numerous applications. Abstract : All‐natural edible protein‐based nanostructures with tunable mesostructures easily transformed from 3D nanonets to 2D thin sheet and to nanoparticles are fabricated by simply dissolving casein micelles and various amounts of rice proteins in an alkaline solution (pH 12) prior to neutralization. The nanostructures can realize controlled bioavailability of encapsulated drugs.